The Demise of the Swiss Interest Rate Puzzle - Peter Kugler; Beatrice Weder di Mauro (University of Basel, Center of Business and Economics (WWZ), 2009)
In this paper we analyzed the violations of UIP for the Swiss Franc against the Dollar, the Euro, the Yen, the Pound and the Canadian Dollar using recent data up to fall 2008. This exercise provides the following main results : first the Swiss interest rate puzzle disappeared, i.e. mean returns on Swiss Franc assets are no longer systematically and significantly lower (as in the 1980 – 1998 sample) when compared jointly with other major currencies in the 1999 to 2008 period. Second and in contrast to earlier evidence we failed to find evidence that geopolitical crises lead to an appreciation of the Swiss Franc in the last ten years. Third even the short run validity of UIP cannot be rejected for the Swiss Franc against the five currencies for the 1999 – 2008 sample. Unfortunately our attempt to locate the time of change and the currencies involved by the application of tests for structural breaks with unknown break point did not lead to clear cut conclusion for the Euro and the Dollar, the two most important foreign currencies from a Swiss perspective.
Keywords: E43; E44; G15; 330; Zinsparität; Schweizer Franken; Vergleich; US-Dollar; Euro; Yen; Pfund Sterling; Schätzung; Schweiz